2018
DOI: 10.1021/acs.jpclett.8b02295
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Photoelectrochemical Device with Open-Circuit Potential Insensitive to Thermodynamic Voltage Loss

Abstract: The open-circuit potential ( V) represents the maximum thermodynamic potential in a device, and achieving a high V is crucial for self-biased photoelectrochemical (PEC) devices that use only solar energy to produce chemical energy. In general, V is limited by the photovoltage ( V), which is a potential difference generated by light-induced thermodynamic processes at semiconductor photoelectrodes, such as the generation and recombination of charge carriers. Therefore, low light intensity and nanostructured semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…When the p-type C@TeNRs are deposited over the n-type SiNWs, it influences the Fermi energy level of the photoelectrode as a result of which the built-in potential changes compared to the pristine SiNWs. V OC is limited by the V ph , which is a potential difference generated by light-induced thermodynamic processes at semiconductor photoelectrodes, such as charge generation, separation, and recombination . The significant contribution to V OC comes from V ph due to the excellent hole transport ability of the TeNRs, which reduces the recombination losses of charge carriers at the TeNR/SiNW interface as well as the photoanode/electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…When the p-type C@TeNRs are deposited over the n-type SiNWs, it influences the Fermi energy level of the photoelectrode as a result of which the built-in potential changes compared to the pristine SiNWs. V OC is limited by the V ph , which is a potential difference generated by light-induced thermodynamic processes at semiconductor photoelectrodes, such as charge generation, separation, and recombination . The significant contribution to V OC comes from V ph due to the excellent hole transport ability of the TeNRs, which reduces the recombination losses of charge carriers at the TeNR/SiNW interface as well as the photoanode/electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…36 As a result of the dynamic change in V fb , the Si photocathode achieved an unexpectedly high V oc of ∼0.75 V. The high V oc was attributed to the abnormal phenomenon of V oc independence from the light- induced potential difference at the semiconductor (i.e., photovoltage, V ph ). 36,37 Despite these findings, the fundamental nature for deriving the dynamic interface energetics and the V ph -independent V oc have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, porous NiO x -integrated p-Si photocathodes for the hydrogen evolution reaction (HER) exhibited dynamic interface energetics in which the flat-band potential ( V fb ) was effectively shifted in the anodic direction as the PEC operation progressed . As a result of the dynamic change in V fb , the Si photocathode achieved an unexpectedly high V oc of ∼0.75 V. The high V oc was attributed to the abnormal phenomenon of V oc independence from the light-induced potential difference at the semiconductor (i.e., photovoltage, V ph ). , Despite these findings, the fundamental nature for deriving the dynamic interface energetics and the V ph -independent V oc have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…When electrocatalysts are integrated on Si photoelectrodes, they are generally considered forming a Schottky-type junction in which a built-in potential is induced by the chemical potential of the electrons (work function). For example, the integration of MoS 2 on p-Si photocathodes to improve the electrocatalytic activity of the hydrogen evolution reaction (HER) has been reported to induce a built-in potential due to the difference in chemical potential between MoS 2 and p-Si. , For n-Si photoanodes, NiO x or CoO x dense thin films have been used as the electrocatalyst for the oxygen evolution reaction (OER) as well as a protective layer against the corrosive electrolyte and have effectively generated high built-in potentials due to their higher chemical potential level relative to n-Si. Recently, It has been reported that a new type of junction distinct from the Schottky junction is formed when an ultrafine nanocrystalline NiO x electrocatalyst (nanocrystal size: 2–5 nm) is deposited on the Si photocathode; , in this new type of junctions, the surface energetics of NiO x predominate over its bulk energetics. In the electrolyte/nanocrystalline NiO x /Si photocathode configuration, as the charge carriers are transferred to the electrolyte to reach the equilibrium state, the transferred charge induces the electrochemical redox reaction of NiO x , transforming it into a NiOOH or Ni­(OH) 2 phase. This redox reaction is accompanied by charge accumulation, which generates an electrochemical potential .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 For n-Si photoanodes, NiO x or CoO x dense thin films have been used as the electrocatalyst for the oxygen evolution reaction (OER) as well as a protective layer against the corrosive electrolyte and have effectively generated high builtin potentials due to their higher chemical potential level relative to n-Si. 31−34 Recently, It has been reported that a new type of junction distinct from the Schottky junction is formed when an ultrafine nanocrystalline NiO x electrocatalyst (nanocrystal size: 2−5 nm) is deposited on the Si photocathode; 39,40 in this new type of junctions, the surface energetics of NiO x predominate over its bulk energetics. 41−44 In the electrolyte/ nanocrystalline NiO x /Si photocathode configuration, as the charge carriers are transferred to the electrolyte to reach the equilibrium state, the transferred charge induces the electrochemical redox reaction of NiO x , transforming it into a NiOOH or Ni(OH) 2 phase.…”
Section: ■ Introductionmentioning
confidence: 99%